Roles of Toll-Like Receptors in Radiotherapy- and Chemotherapy-Induced Oral Mucositis: A Concise Review - Ji, Ling; Hao, Siyuan; Wang, Jiantao; Zou, Jing; Wang, Yan (Frontiers in Cellular and Infection Microbiology, 2022)
Radiotherapy and/or chemotherapy-induced oral mucositis (RIOM/CIOM) is a common complication in cancer patients, leading to negative clinical manifestations, reduced quality of life, and impacting compliance with anticancer treatment. The composition and metabolic function of the oral microbiome, as well as the innate immune response of the oral mucosa are severely altered during chemotherapy or radiotherapy, promoting the expression of inflammatory mediators by direct and indirect mechanisms. Commensal oral bacteria-mediated innate immune signaling via Toll-like receptors (TLRs) ambiguously shapes radiotherapy- and/or chemotherapy-induced oral damage. To date, there has been no comprehensive overview of the role of TLRs in RIOM/CIOM. This review aims to provide a narrative of the involvement of TLRs, including TLR2, TLR4, TLR5, and TLR9, in RIOM/CIOM, mainly by mediating the interaction between the host and microorganisms. As such, we suggest that these TLR signaling pathways are a novel mechanism of RIOM/CIOM with considerable potential for use in therapeutic interventions. More studies are needed in the future to investigate the role of different TLRs in RIOM/CIOM to provide a reference for the precise control of RIOM/CIOM.